Survey of Pedagogical Knowledge and Satisfaction Index among Teachers at Sekolah Rendah Islam Ibnu ‘Abbas - Saiful Hakim, Mahyiddin; Shakinah, Sukardhi; Mohd Rusllim, Mohamed; Mohd. Shafie, Bakar; Ahmad Johari, Mohamad; Johari, Surif (Knowledge Transfer Centre, USM, 2016)
The aim of this study was to look at the understanding of pedagogical knowledge, job satisfaction among primary school teachers of Sekolah Rendah Islam Ibnu Abbas Kuantan. To achieve this, the perception and practice of pedagogical knowledge of teachers were identified. A total of 19 teachers at the school were involved as respondents in this study. Data were collected through a questionnaire consisting of 41 items of Likert scale. Data were analyzed using descriptive statistics. The result of this study shows that teachers have the knowledge, skills and application of good pedagogical knowledge. Nevertheless, for the method or approach during teaching and learning, teachers still did not planned carefully before teaching and learning takes place. Teachers show lack of clarification of objectives as well as perform demonstration to the students when it was required. In terms of jobs satisfaction, number of teachers mentioned they were concerns of the support from the employer, especially financial support, and basic amenities. Thus, it is expected that the findings of this study can be used as a process to carry out improvements to the school and the administration in maintaining the quality and reputation of all parties.